GENE-20. IDENTIFYING POTENTIAL GENES AND MECHANISMS DRIVING IDH-MUTANT GLIOMA PROGRESSION AND RECURRENCE THROUGH RNA-SEQUENCING. (11th November 2019) - Cho, Angela; Hudson, Amanda; Colvin, Emily; Hayes, Sarah; Wheeler, Helen; Howell, Viive
Abstract: Gliomas are the most common primary brain tumors in adults. IDH -mutated low-grade gliomas of astrocytic lineage (astrocytomas) have a relatively indolent clinical course; however, over time they progress to a higher grade. Molecular studies revealed recurrent tumors harbor more mutations upon malignant progression when treated with chemotherapy and/or radiotherapy compared to treatment-naïve tumors. However, genes which promote progression and recurrence in these tumors are unknown. This study aims to identify the transcriptional drivers of progression and recurrence of IDH -mutant gliomas. Longitudinal comparison of transcriptional profiles was performed on 6 matched pairs of primary lesions and their higher-grade recurrent lesion collected 1 to 8 years later. Three patients received no treatment and three patients received radiotherapy alone between their first and second surgeries. RNA was extracted from frozen specimens and following quality control, analyzed with the Illumina Next-Generation Sequencing platform (HiSeq HT paired end, TruSeq Kit). Comparison of RNA-seq results from primary and recurrent specimens identified 2042 differentially expressed genes (FC ≥2) for the no-treatment group and 2066 differentially expressed genes for the radiotherapy group. These genes include CADM2, SPP1, NDRG2 and CA9 which are associated with pro-tumor processes such as signal transduction, cell adhesion and treatment resistance. Validation is in progress. Identifying key genes driving glioma progression and recurrence will increase our understanding of the nature of these tumors and reveal core processes and potential novel targets that may be exploited for additional therapies for this deadly cancer.